High performance and sustainable CNF membrane via facile in-situ envelopment of hydrochar for water treatment. (15th November 2022) - Pak, Sewon; Ahn, Jungbin; Kim, Hyungsup
Abstract: In this study, cellulose nanofiber (CNF) membranes for water treatment are prepared via in-situ hydrothermal carbonization of glucose in a CNF suspension. The in-situ carbonized CNFs were fabricated into the membranes via dead-end filtration under hydraulic pressure (1 bar). The in-situ carbonized CNF membranes showed high pure water flux (56.25 L·h −1 ·m −2 ) without critical flux drop for 12 h of membrane fabrication. The hydrochar chemically bonded with CNF enhanced the durability of CNF during membrane fabrication. Owing to the strong and stable electrostatic interaction between the target dye and hydrochar, the in-situ carbonized membrane also displayed excellent dye rejection for dilute and concentrated solutions, with high selectivity and good reusability. This study provides a successful strategy for fabricating an all-carbohydrate-based high-performance water treatment membrane. Graphical abstract: Unlabelled Image